The ANALISIS STILISTIKA DAN SEMIOTIKA DALAM LAGU POP BALI YANG BERJUDUL ANGKIHAN BAAN NYILIH - Ni Komang Aryani Aryani; Ni Wayan Apriani; I Wayan Jatiyasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This study has two objectives, namely to describe stylistics and semiotics in the lyrics of the song entitled